2016
DOI: 10.1007/s10753-016-0370-y
|View full text |Cite
|
Sign up to set email alerts
|

PGRN Suppresses Inflammation and Promotes Autophagy in Keratinocytes Through the Wnt/β-Catenin Signaling Pathway

Abstract: Psoriasis is a chronic, immune-mediated inflammatory skin disease that has a major impact on patients' quality of life. Progranulin (PGRN) is highly expressed in skin diseases and plays an important role in inflammation response and autophagy. However, the function of PGRN in the immune system and autophagy in psoriasis has not been clearly identified and elaborated on. Thus, this study aimed to investigate the role of PGRN on the inflammatory and autophagy process underlying inflammation in HaCaT cells. We sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 39 publications
2
35
0
Order By: Relevance
“…In the current study, there was a significant stepwise upregulation of PGRN from normal skin of controls passing to perilesional and ended by lesional psoriatic skin in psoriasis patients. In agreement with our results, Tian et al reported that PGRN was significantly upregulated in lesional skin from psoriasis patients (n = 11) than perilesional skin (n = 8) and biopsies from healthy individuals (n = 9). Additionally, Huang et al demonstrated that PGRN protein and mRNA expression levels were significantly higher in psoriatic lesions than controls.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the current study, there was a significant stepwise upregulation of PGRN from normal skin of controls passing to perilesional and ended by lesional psoriatic skin in psoriasis patients. In agreement with our results, Tian et al reported that PGRN was significantly upregulated in lesional skin from psoriasis patients (n = 11) than perilesional skin (n = 8) and biopsies from healthy individuals (n = 9). Additionally, Huang et al demonstrated that PGRN protein and mRNA expression levels were significantly higher in psoriatic lesions than controls.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, progranulin was negatively correlated with β‐catenin expression in perilesional and lesional psoriatic skin, suggesting that pro‐inflammatory effect of progranulin in psoriasis may be mediate through decreasing β‐catenin expression in psoriasis. Parallel to our observation, Tian et al through their in vitro study using culture HaCat cells reported that PGRN inhibited the activity of β‐catenin signaling pathway, and its target genes cyclin D1 and c‐myc. Also, in degenerative arthritis, PGRN inhibited the activation of β‐catenin signaling in chondrocytes …”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Autophagy is a highly regulated process that is involved in many pathophysiological situations, including cerebral ischemia/reperfusion injury . Autophagy has been considered a double‐edged sword with prosurvival or prodeath potential in cerebral ischemia/reperfusion injury .…”
Section: Discussionmentioning
confidence: 99%
“…* P<0.05 and *** P<0.001. miR, microRNA. the overexpression of progranulin inhibited TNF-α-induced inflammation in keratinocytes by positively mediating autophagy through the Wnt/β-catenin signaling pathway (25). More studies are required to elucidate the detailed role of β-catenin in the miR-24-mediated inhibition of autophagy.…”
Section: Discussionmentioning
confidence: 99%